Language Model of Male and Female Students (Sociolinguistic Study) - Halimah Tussa’diah; Wulandari Siregar; Muhammad Hasyimsyah Batubara (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
This research discusses and raises the theme of studying the language model of male and female students in a sociolinguistic study. Language plays an important role in interaction and communication. Both male and female speakers have their speaking skills, especially on important matters. This research was conducted with a descriptive qualitative approach. In the steps to analyze the data, researchers used several stages such as data selection, data grouping, and concluding the data being analyzed. The language and conversation models between male and female students have fundamental differences. According to observations, female students seem more verbal than male students. Furthermore, the language of male students is more confrontational, informative, to the point, giving advice, sarcastic, and joking. Meanwhile, the language of female students is more supportive, giving and seeking understanding, using personal feelings, caring, togetherness, and being serious.